Substitute location : semiotics and perception of substitute location : in fiction film : A Road Movie - Behrens, Thomas (2016)
Tese de doutoramento, Belas-Artes (Audiovisuais), Universidade de Lisboa, Faculdade de Belas-Artes, 2016